FIRST RECORD OF Brachymeria podagrica (HYMENOPTERA: CHALCIDIDAE) AS PARASITOID OF Peckia collusor (DIPTERA: SARCOPHAGIDAE) (2021)
In this work, the wasp Brachymeria podagrica is recorded for the first time for Colombia, a solitary parasitoid of larvae of the Peckia collusor fly. Third instar larvae of P. collusor were exposed to outdoor ambient conditions for 6 hours in the garden of the Tecnológico de Antioquia (Medellín, Colombia). 29 B. podagrica adults were obtained from the host pupae. Prevalence of parasitism was 14.5 %. Keywords: flesh flies, natural enemy, parasite